P446 Patient and public involvement in a clinical trial for perianal Crohn's fistula. (16th January 2018) - Sahnan, K; Verjee, A; Blackwell, S; Sawyer, R; Mannick, S; Lee, M J; Adegbola, S O; Tozer, P J; Heywood, N; Hart, A L; Fearnhead, N S
Abstract: Background: The James Lind Alliance agreed a research agenda in IBD, involving 400 patients, carers and charitable representatives. "What is an optimal treatment strategy for perianal Crohn's disease and what individual factors determine this?" was prioritised fifth on the IBD research agenda. 1 This question is now the subject of the EvaluatiNg Goal Directed MAnagement (ENiGMA) trial for patients' with fistulising perianal Crohn's Disease (pCD). Methods: Four patient co-applicants have been integral to all meetings and teleconferences of the ENiGMA study group. These patients have influenced trial design and help prioritise outcomes, Figure 1. Results: (a) Initiation of the trial: A formal patient and public involvement exercise was carried out to present the trial proposal to 23 patients with perianal Crohn's fistula and to assess their views on all aspects of the study. Patients agreed that a prospective cohort study design would-be easy to recruit to, indicating that they may even wish to transfer care between institutions to allow participation. Quality of life and patient-reported outcomes were felt to be important and patients attending felt MYMOP, a method to allow patients to set their own treatment goals, should be introduced into routine clinical practice as a means of exploring patients' wishes in a structured way. The burden of the suggested questionnaires was deemed reasonable and patients completed the questionnaires within 15 min. In addition, an anonymised perineal photograph, as means of classifying the type/stage of fistulising pCD, was deemed both acceptable and useful. (b) Development of the trial: Two separate workstreams were developed from the initial PPI involvement day. The first was a core outcome set for fistulising pCD, which has recently been submitted for publication and involved 83 patients within one of the three stakeholder groups. The second was the development of a specific Crohn's anal fistula quality of life (CaF-QoL) score. CaF-QoL is in the second phase (of five) of development and is due to be completed in April 2018. (c) Future directions: The ENiGMA study includes the final consensus of front-running options in trial development; patients will form one of the three stakeholder groups in final trial design. One of our patient representatives (SB) edits the ENiGMA Collaboration's newsletter. Conclusions: Patients and representatives of patient groups have been partners in ENiGMA from conception through study development and design, and remain integral to delivery of this study proposal. Reference: 1. Hart AL et al. What are the top 10 research questions in the treatment of inflammatory bowel disease? A priority setting partnership with the James Lind alliance. J Crohns Colitis, 2017.